(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to develop an adaptation model for assessing Project Management Maturity (PMM) in medium and large Saudi contracting firms and to test its impact on the efficiency of urban project delivery within the context of Vision 2030. The theoretical framework was based on the ten principles of the Project Management Institute (PMI) from the PMBOK® Guide Seventh Edition, proposing a "Layered Adaptation Model" that categorizes principles into universal, adaptable, and foundational. Employing a quantitative methodology, a contextually adapted questionnaire was distributed to a stratified random sample of 285 project managers and practitioners in the contracting sector. Statistical analysis results (Multiple Regression, Correlation Coefficient) revealed a statistically significant positive relationship between the level of project management maturity (overall score and sub-dimensions) and efficiency indicators (adherence to schedule, budget, and output quality), with a correlation coefficient of (r = 0.74). Regression analysis showed that the "adaptable" dimension (e.g., principles of leadership, steering, and adaptability) had the greatest impact (β = 0.41). The results also indicated statistically significant differences in favor of large companies in overall maturity levels. The study proposes a practical integrative model consisting of a diagnostic mechanism (self-assessment tool) and a graduated development roadmap. The study concludes that the contextualized and principled adoption of global project management standards, not literal application, is the critical factor in enhancing project efficiency. It recommends the adoption of this model by regulatory bodies and contracting companies to better align with the strategic objectives of Vision 2030.